Performance of 3D-printed samples based on starch treated by radio frequency energy. (May 2023) - Ma, Shu; Zhang, Qianru; Lin, Qian; Pan, Lin; Yu, Xiuzhu; Jiang, Hao
Abstract: In this study, we investigated changes in the chain length distribution, molecular weight distribution, amylose content, microstructures, thermal properties and rheological properties of potato starch following radio frequency (RF) electromagnetic fields exposure with varying moisture content (30, 40, 50, 60, 70%, w /w). We identified a RF-modified moisture content suitable for 3D printing. Our results showed that RF treatment roughened the starch surface and broke down the longer chains into shorter ones, which reduced the molecular weight, viscosity, and pasting temperature of the starch. The RF-treated starch gels showed better printing performance than untreated potato gels. In addition, changes in the physicochemical properties of the starch became more pronounced with increasing moisture content. Gels made from starch with 70% moisture content treated with RF energy provided the best morphological indicators, including clarity line uniformity and high retention rate. Overall, RF treatment of starch with varying moisture content is an effective method for preparing starch gels for 3D printing. Highlights: The relationship between structure of starch and 3D printed products was revealed. Short chain ratio in amylopectin increased after radio frequency (RF) treatment. RF treatment break amylopectin as amylose content increase in starch. The reduce of amylose molecular weight benefited to 3D-printed effect of gels. 3D printed products were best after RF treatment at high moisture content.